Evaluating a decade of World Bank gender policy, 1990-99 (World Bank e-Library., 2005)
As part of the Bank's poverty reduction mandate, the Bank's 1994 Operational Policy on Gender Dimensions of Development aimed to reduce gender disparity and increase the participation of women in the economic development of their countries. This evaluation examines the relevance and results of this policy.